Application of Arachis hypogaea as natural coagulant for turbidity removal - Owaidhah A.B.R.; Hayder G.; Hung Y.-T. (Inderscience Publishers, 2024)
Natural water systems are contaminated by various point and non-point sources because of industrialisation, urbanisation and other developmental activities. Pollutants that enter the water changes the water physical, chemical and biological properties. In addition, most of the materials used in the water treatment during coagulation are chemicals. However, the long and short-term effect of chemical encouraged researchers to look into other options for natural coagulants. In this study, Arachis hypogaea was used to remove turbidity from synthetic wastewater. During lab experiment, synthetic wastewater was adjusted to different initial turbidity of 5.02, 50.4 and 150 NTU, and jar test was used to define the optimum type of stock solution. The results obtained from the study shows that the Arachis hypogaea decreased the turbidity from 150 to 5.87 NTU. This implies that Arachis hypogaea can be used as a natural coagulant in replacement of chemical coagulants to improve water quality. Copyright 2023 Inderscience Enterprises Ltd.